A retrospective study of bitches with pyometra and mucometra medically treated with aglepristone - Ros, Linnea (SLU/Dept. of Clinical Sciences (until 231231), 2014)
Pyometra is a common and life threatening disease of intact bitches. The disease is caused by a hormonal influence on the uterus in combination with a bacterial infection. The most common treatment is ovariohysterectomy, but several medical options are available to maintain fertility or avoid surgery and anaesthesia. Drugs that can be used for medical treatment are for example progesterone-receptor antagonists, prostaglandins and dopamine agonist. The present study focused on treatment with the progesterone-receptor antagonistaglepristone in combination with antimicrobial therapy. There are few studies evaluating the long-term outcome after medical treatment with aglepristone, and the outcome and recurrence risk varies. The aim of this study was to evaluate long-term recovery and fertility after treatment with aglepristone in bitches with pyometra. In this study 30 bitches with pyometra or mucometra that were admitted to and treated at the University Animal Hospital (UDS), Swedish University of Agricultural Sciences (SLU) during a 9-year-period were included. The UDS data records were studied retrospectively and the outcome followed up by telephone interviews with the owners. The bitches were treated with aglepristone at a dose 10 mg/kg sc with a median of 4 times (12/28 bitches). All but one bitch were also treated with antimicrobial drugs for a mean duration of 22 days and the most frequently used antimicrobial drug was enrofloxacin. Escherichia coli were the most commonly isolated bacteria. None of the bacterial strains cultured were resistant to enrofloxacin, but 9 % were resistant to trimetoprim/sulfa. The outcome was determined up to 6 years after treatment. The success rate, determined as a clinically healthy status, was 77 % (23/30 bitches), and the recurrence rate was 43 % (10/23 bitches) defined as recurrence of the disease. The mean time until recurrence was 11 months after the end of treatment. After treatment, 71 % (n = 10) of the 14 mated bitches produced puppies, and five of them produced two to four litters. The bitches that did not have a successful treatment were ovariohysterectomized, in all cases but one which was euthanized. In conclusion, medical treatment with aglepristone in combination with antimicrobial therapy was successful in 77% of the bitches studied and the recurrence rate was 43%.